Molecular Characterization of Trypanosoma cruzi from Triatomine Species in São Paulo State, an Area Free of Vector-Borne Chagas Disease - Eliana Ferreira Monteiro; Rubens Antonio da Silva; Arlei Marcili; Karin Kirchgatter (Insects)
Chagas disease (ChD) is a neglected tropical disease caused by Trypanosoma cruzi, endemic in 21 countries across the Americas, with increasing cases globally. In São Paulo, Brazil, vector control has focused on Triatoma infestans, but secondary triatomine species continue to pose transmission risks. This study aimed to investigate the prevalence of T. cruzi in triatomine feces and characterize its genetic diversity using molecular techniques. Fecal samples were collected from 570 triatomines across 25 municipalities in São Paulo, followed by DNA extraction and PCR amplification targeting the mitochondrial cytochrome b gene and the V7V8 region of the 18S rRNA gene. The results revealed a low overall infection rate (3.2%). However, excluding the triatomines collected in palm trees, all of which were negative, we found mainly Panstrongylus megistus in residences and peridomiciles, showing the highest infection rate (65%) for T. cruzi, followed by Triatoma sordida and Rhodnius neglectus. Phylogenetic analysis confirmed that DTU TcI was the most prevalent genotype, consistent with previous findings in the region. This study highlights the importance of continued vector surveillance, as these secondary species are capable of maintaining T. cruzi transmission in both urban and rural environments, underscoring the ongoing risk of ChD resurgence in São Paulo.